Constitutional Question: Alternatif Baru Pelindungan Hak Konstitusional Warga Negara Melalui Concrete Review di Indonesia (Constitutional Question: New Alternative to Protect Citizen’s Constitutional Right From Concrete Review in Indonesia) - Xavier Nugraha; Ave Maria Frisa Katherina; Safira Noor Ramadhanty; Elma Putri Tanbun (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2019)
The authority of the Constitutional Court in the current regulations in Indonesia still does not fully protect the constitutional rights of the citizens. This is reflected by seeing that the examination that were accommodated only covered the abstract review (there were no concrete cases in the court). This condition causes the absence of legal remedies to resolve the issue of constitutionality of legal norms in the court (concrete review), even though often the issue of constitutionality of laws is precisely found in court proceedings. This research is a dogmatic legal research. The primary legal material usedis the Law of the Constitutional Court, whilst the secondary legal material consists of books, journals, and other relevant sourcesrelated to the issues discussed in this research. Based on this research, it was found that it is necessary to raise a constitutional question so that the Acts that are being examined can be annuled by the Constitutional Court and articles that are considered in contrary to the constitution cannot be used as a basis by the judge to decide related cases that being examined concretely. AbstrakWewenang Mahkamah Konstitusi yang ada dalam peraturan perundang-undangan di Indonesia saat ini masih belum melindungi hak-hak konstitusional warga negara secara penuh. Hal ini tercermin dari pengujian yang diakomodasi hanyalah melingkupi abstract review (belum adanya kasus konkrit di pengadilan). Kondisi ini menyebabkan tidak adanya upaya hukum menyelesaikan persoalan konstitusionalitas norma hukum di pengadilan (concrete review), padahal sering kali persoalan konstitusionalitas undang-undang justru ditemukan dari proses di pengadilan. Penelitian ini merupakan penelitian hukum dogmatik. Bahan hukum primer yang digunakan yaitu Undang-Undang Mahkamah Konstitusi, sedangkan bahan hukum sekunder terdiri dari buku, jurnal, dan sumber lain yang relevan dengan masalah yang dibahas dalam penelitian ini. Berdasarkan penelitian ini, ditemukan bahwa perlu diterapkannya constitutional question supaya undang-undang yang diujikan dapat dibatalkan oleh Mahkamah Konstitusi dan pasal yang dinilai bertentangan dengan konstitusi tersebut tidak dapat dijadikan dasar oleh hakim untuk memutus terkait kasus yang diujikan secara konkrit.